1957
DOI: 10.1017/s0022172400037219
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusin the infant upper respiratory tract: I. Observations on hospital-born babies

Abstract: Pernasal and throat swabs taken on 106 newborn babies showed that 99% harboured coagulase-positiveStaph. aureusby the time they left the hospital nursery. When the strains isolated from thirty-four of them were phage typed and tested for penicillin sensitivity, it was found that thirty-three (97%) carried at least one penicillin-resistant strain. Phage typing of their subsequent cultures, taken as they became older, demonstrated that they retained these strains for very long periods. Of the twenty-one still un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1959
1959
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 16 publications
(14 reference statements)
2
9
0
Order By: Relevance
“…aureus on these two occasions was associated more frequently than could be explained by chance even though the organisms were usually of different phage types. This confirms the observations of 129 9 HYG 8Ic Hurst (1957) that 'babies who do not become carriers within the first 2 months of life are unlikely to do so later'. It also suggests that the carrier state is not necessarily dependant upon the type of Staph.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…aureus on these two occasions was associated more frequently than could be explained by chance even though the organisms were usually of different phage types. This confirms the observations of 129 9 HYG 8Ic Hurst (1957) that 'babies who do not become carriers within the first 2 months of life are unlikely to do so later'. It also suggests that the carrier state is not necessarily dependant upon the type of Staph.…”
Section: Resultssupporting
confidence: 89%
“…aureus in their noses, and the majority of these bacteria were resistant to penicillin (Barber et al 1953;Hurst, 1957;Williams, 1961). It was suggested that 'antibiotic-resistant strains among the general non-hospital population will be increased steadily by babies born in hospital' (Hurst, 1957). In 1962 Miller, Galbraith & Green endeavoured to relate the carriage of resistant staphylococci to the recent history of the subjects concerned and concluded that admission to hospital was the major factor.…”
Section: Introductionmentioning
confidence: 99%
“…193 By the fifth day of life, 40% to 90% of the infants in the nursery will be colonized with S. aureus. Localized infection can be impetigo, pustulosis in neonates, cellulitis, or wound infection, and invasive or suppurative disease includes sepsis, pneumonia, osteomyelitis, arthritis, and endocarditis.…”
Section: Staphylococcal Infectionsmentioning
confidence: 99%
“…The results obtained at 5 years were compared with those from the same children when they were swabbed the first time and also at one year, since it has been suggested (Hurst, 1957) that 'babies who do not become carriers within the first two months of life are unlikely to do so later'. In fact there was little relationship between the results of the swabs taken during the first year of life and those at five years.…”
Section: Discussionmentioning
confidence: 99%